PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG KMP. SANGKE PALANGGA DI PELABUHAN PENYEBERANGAN BIRA-JAMPEA-LABUAN BAJO PT. ASDP INDONESIA FERRY (PERSERO) CABANG SELAYAR PADA MASA PANDEMI COVID-19 - Nurul Wahyuni; Muh. Ichwan Musa; Muhammad Ilham Wardhana Haeruddin; Romansyah Sahabuddin; Zainal Ruma (Lafadz Jaya Publisher, 2023)
Study this aim for know Influence Proof Physical, Reliability, Power Response, Guarantee and Empathy in a manner Partial and simultaneous To Satisfaction passenger’s camp. Sangke Palangga in the Harbour Crossing Bira - Jampea -Labuan Bajo PT. ASDP Indonesia Ferry (Persero) Branch Selayar on Period Covid-19 pandemic. Type study is Quantitative. Study this use Approach descriptive. Population study this is whole passenger’s camp. Sangke Palangga in the harbour crossing Bira-Jampea-Labuan Bajo PT. ASDP Indonesia Ferry (Persero) branch Selayar a total of 14,736 people were taken from 2020 to with 2021 on period the covid-19 pandemic. And samples on study this is 100 people. Technique data collection carried out with share questionnaire. The technique of data analysis used is analysis multiple linear regression with use Statistical Product Service Solution (SPSS) version 13. The results of study this show that variable proof physical there is influence positive and significant in a manner Partial to satisfaction passenger. Variable reliability there is influence positive and significant in a manner Partial to satisfaction passenger. Variable power responsive there is influence positive and significant in a manner Partial to satisfaction passenger. Variable guarantee there is influence positive and significant in a manner Partial to satisfaction passenger. Variable empathy there is influence positive and s significant in a manner Partial to satisfaction passenger. Variable proof physical, reliability, power response, guarantee and empathy there is influence positive and significant in a manner simultaneous to satisfaction passenger.